Geology and litogeochemistry of the itaoca batholith, south of sÃo paulo state - Zenero, Jonas Menezes [UNESP]; Vieira, Otávio Augusto Ruiz Paccola [UNESP]; Godoy, Antonio Misson [UNESP] (UNESP - Universidade Estadual Paulista, 2020)
The Itaoca Batholith constitutes an intrusive circular shape body, of 200 km2, located in the south limit between the São Paulo and Paraná states, in the Apiaí Topographic Map. It is associated with the Central Mantiqueira Province and correlated with the Apiaí Terrain neoproterozoic evolution. The embedding rocks are constituted by the Lajeado Group's metavolcanicsedimentary sequence belonging to the Açungui Supergroup, besides presenting in the surrounding of the magmatic body and in the ceiling-pendants, rocks in epidote to pyroxene hornfels facies, in addition to superimposed hydrated mineralogies associated with the Ribeira Shear Zone. The batholith rocks were divided into two units, named Itaoca and Ribeira, the first one gray color and the second pink. The two units were subdivided into 6 facies, one represented by an undifferentiated facies association. Petrographically, its rocks basically constitute biotite-hornblende-quartz monzonite to monzogranite, holo-to leucocratic, porphyritic of medium to coarse granulation, isotropic to suboriented. The Itaoca Unit is made up of less evolved rocks (quartz monzonite) and, possibly, it is a primary magmatic pulse compared to the Ribeira Unit, which is more differentiated (monzogranite). These granitoid rocks have a calcium alkaline, peraluminous character, I cordilleran type, syn-to late collisional of a magmatic arc environment and generated by the fusion of lower crust rocks.
Geologia e litogeoquimica do batólito itaoca, sul do estado de são paulo
Keywords: Geology; Granites; Itaoca; Lithogeochemistry